2018
DOI: 10.1039/c8ra06722h
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and characterization of novel chromone based-copper(ii) antitumor agents with N,N-donor ligands: comparative DNA/RNA binding profile and cytotoxicity

Abstract: New chromone-based Cu(ii) tRNA targeted complexes 1–3 as potential anticancer agents have been synthesized and thoroughly characterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 94 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…Keeping in mind the complexity of cancers which show diverse phenotypes and multiple etiologies, a one-size-fits-all drug design strategy for the development of cancer chemotherapeutics does not yield successful results. Lately, Arjmand et al [47] adopted a series of methods, such as the combination of X-ray crystal structures and molecular docking, to design, synthesize, and characterize novel chromone based-copper(II) antitumor inhibitors. In general, after obtaining the structure of the receptor macromolecule by x-crystal single-crystal diffraction technique or multi-dimensional NMR, molecular modeling software can be used to analyze the physicochemical properties of drug binding sites on the receptor, especially including electrostatic field, hydrophobic field, hydrogen bond, and key residues.…”
Section: Structure-based Drug Designmentioning
confidence: 99%
“…Keeping in mind the complexity of cancers which show diverse phenotypes and multiple etiologies, a one-size-fits-all drug design strategy for the development of cancer chemotherapeutics does not yield successful results. Lately, Arjmand et al [47] adopted a series of methods, such as the combination of X-ray crystal structures and molecular docking, to design, synthesize, and characterize novel chromone based-copper(II) antitumor inhibitors. In general, after obtaining the structure of the receptor macromolecule by x-crystal single-crystal diffraction technique or multi-dimensional NMR, molecular modeling software can be used to analyze the physicochemical properties of drug binding sites on the receptor, especially including electrostatic field, hydrophobic field, hydrogen bond, and key residues.…”
Section: Structure-based Drug Designmentioning
confidence: 99%
“…The enhancement in the emission intensity arises due to the penetration of complexes into the hydrophobic environment of interior tRNA/ctDNA helixes as has been reported in many research articles describing the interaction studies of small molecules with nucleic acids. [41][42][43] As studies revealed greater binding propensity for tRNA as compared to ctDNA which could be attributed to the conformation of RNA having an L-shaped tertiary structure, where nucleobases are pushed outwards from the helix axis in the minor groove direction and tilted substantially with respect to the helix axis, funneling the complexes to the interior of the narrow grooves of RNA. Furthermore binding strength of 1 and 2 was quantied by employing the Scatchard equation 44 and the evaluated data is shown in Table 1.…”
Section: Interaction Studies With Nucleic Acids (Dna and Rna)mentioning
confidence: 99%
“…[6,7] Moreover, chromone-based metallodrugs are known to inhibit various types of cancer targets viz., DNA, tRNAs, kinase inhibitor enzymes and topoisomerases. [8][9][10] Zn(II) in chromone-appended ligand framework can be explored as an antitumor agent due to its capability to mediate cleavage of the phosphate diester backbone, redox inertness, Lewis acidity, and rapid ligand exchange. [11] Chelation of Zn(II) to naturally occurring chromone improves the complex's planar functionality thereby, allowing the complex to insert and stack between base pairs of double-helical DNA more readily than the free ligand.…”
Section: Introductionmentioning
confidence: 99%